5S methodology to improve the performance of the warehouse a sugar company in Peru - JUÁREZ ELEORRAGA, Ketty Aracelly (2021)
The present research had the general objective of proposing the 5S methodology to improve the performance of the warehouse of a sugar company in Peru. The formulation of the problem was presented under the following question: How should the proposal of the 5S methodology be to improve the performance of the warehouse of a sugar company in Peru? The study is of a non-experimental design, descriptive, projective; for the compilation of information, aquestionnaire applied to a sample of 24 warehouse workers was used. The results of the research showed that, with respect to the diagnosis of the needs to improve the warehouse, it was determined that 54% of the respondents indicate that there are unnecessary elements in the warehouse, which makes the management and control of resources difficult. In addition, with respect to the level of performance, 42% of those surveyed stated that they were inagreement with the established processes. In conclusion, the design of the 5S methodology proposal allows to improve performance in a sugar company in Peru, which must be based on the classification of the stocks present in the warehouse.Keywords: Warehouse, 5s methodology, proposal, performance.